Evaluation of Antibiotic Use in Dengue Fever Patients Using the ATC/DDD Method at HKBP Hospital - Hepni, Hepni; Yanti, Fitri; Wastuti, Sri; Siahaan, Naya Fortuna Dewi (International Journal on Health and Medical Sciences, 2025)
Infectious diseases are diseases caused by the entry and growth of microorganisms, one of which is pathogenic bacteria (Novard et al., 2019). High use of antibiotics for infectious diseases increases the risk of irrational antibiotic use which can result in the therapeutic goal not being achieved. This study aims to determine based on patient characteristics, the profile of antibiotic use in hospitalized patients at RSU. HKBP Balige and the quantity of antibiotic use in DDD units. This study is observational (non-experimental) which was conducted retrospectively using data obtained from the Hospital Information System (SIRS) for the period January-April 2024 in the form of drug names, dosage forms, dosage strengths, quantity of use, number of hospitalized patients per month, length of hospitalization. Data analysis in this study used the quantitative Anatomical Therapeutic Chemical (ATC) / Defined Daily Dose (DDD) and Drug Utilization 90% (DU90%) methods. The results of the study showed that there were 2 types of antibiotics used in dengue fever patients during 2024 with an average total usage value of 280.07 DDD/100 HR. The most widely used types of antibiotics were cefixime (66.70%) and cefotaxime (33.30%), and the most common route of antibiotic administration was intravenous, and the most frequent duration of antibiotic therapy was <3 days (85.71%).